2013
DOI: 10.1371/journal.pone.0077212
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Degrading Enzyme Activities Stimulated by Increased Nutrient Availability in Arctic Tundra Soils

Abstract: Climate-induced warming of the Arctic tundra is expected to increase nutrient availability to soil microbes, which in turn may accelerate soil organic matter (SOM) decomposition. We increased nutrient availability via fertilization to investigate the microbial response via soil enzyme activities. Specifically, we measured potential activities of seven enzymes at four temperatures in three soil profiles (organic, organic/mineral interface, and mineral) from untreated native soils and from soils which had been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 87 publications
3
49
3
Order By: Relevance
“…This result did not support the resource allocation theory Keeler et al, 2008), which predicted that N addition would increase the activities of C-and P-cycling enzymes, but suppress the activity of N-cycling enzymes. The lack of a N addition effect on soil enzymes in this study was unexpected, given that the amount of N we added was at the high end of N-addition experiments and that a positive effect of N addition on C-and P-acquiring enzymes has often been observed in other ecosystems (e.g., Koyama et al, 2013;Saiya-Cork et al, 2002;Wang et al, 2008). However, Bell et al (2010) also found that soil enzyme activity was unresponsive to N addition across all seasons in a temperate old field.…”
Section: Neutral Effect Of N Addition On Soil Enzymesmentioning
confidence: 54%
See 1 more Smart Citation
“…This result did not support the resource allocation theory Keeler et al, 2008), which predicted that N addition would increase the activities of C-and P-cycling enzymes, but suppress the activity of N-cycling enzymes. The lack of a N addition effect on soil enzymes in this study was unexpected, given that the amount of N we added was at the high end of N-addition experiments and that a positive effect of N addition on C-and P-acquiring enzymes has often been observed in other ecosystems (e.g., Koyama et al, 2013;Saiya-Cork et al, 2002;Wang et al, 2008). However, Bell et al (2010) also found that soil enzyme activity was unresponsive to N addition across all seasons in a temperate old field.…”
Section: Neutral Effect Of N Addition On Soil Enzymesmentioning
confidence: 54%
“…Increased nutrient availability often has multiple effects on aboveground organisms, including biodiversity loss (Hooper et al, 2012) and their associated ecosystem functioning and services (Isbell et al, 2013;Smith et al, 1999). Meanwhile, nutrient availability can be amplified by climate warming by enhancing microbial decomposition of soil organic matter (Bardgett et al, 2008) which, in turn, stimulates plant growth and mediates ecosystem carbon storage (Koyama et al, 2013;Mack et al, 2004;Waldrop et al, 2004). However, the responses of belowground microorganisms to nutrient addition remains poorly understood (Leff et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…), including these same soils with NP addition in an earlier study (Koyama et al. ). In fact, this P‐acquisition response to P amendments is more common than C‐ or N‐acquisition responses in the literature (reviewed in Burns et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Koyama et al. ), and to a limited extent, above‐ and belowground combined (Chapin et al. , Gough et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, these values of sensitivity to temperature correspond to the cold‐adapted communities and enzymes of Arctic seawater, and they are expected to be higher than those of temperate waters since cold‐adapted enzymes tend to be more responsive to increasing temperature than warm‐adapted enzymes (German, Marcelo, Stone, & Allison, ). Additional information about the sensitivity to temperature of βG activity is available from studies of terrestrial systems ( E a ranging 0.27–0.72 eV, (Trasar‐Cepeda, Gil‐Sotres, & Leirós, ; Wallenstein, Mcmahon, & Schimel, ; German et al., ; Stone et al., ; Steinweg, Jagadanna, Frerichs, & Mayes, ; Koyama, Wallenstein, Simpson, & Moore, ; Bárta, Šlajsová, Tahovská, Picek, & Šantrůčková, )) while much fewer data are available for LAP ( E a ranging −0.33 to 0.62 eV, (Wallenstein et al., ; Koyama et al., ; Bárta et al., )) or AP ( E a ranging 0.39–0.48 eV, (Bárta et al., )). Maybe the striking lack of data for marine systems arises from the general consideration of the temperature as a sparse driver of the extracellular enzyme activity when characterizing the carbon and nutrient cycling in the marine environments (Arnosti et al., ) while being considered as fundamental driver in terrestrial systems.…”
Section: Introductionmentioning
confidence: 99%